Intestinal permeability after single dose gluten challenge in coeliac disease. Issue 7 (July 1991) - Greco, L; D'Adamo, G; Truscelli, A; Parrilli, G; Mayer, M; Budillon, G
Abstract : The changes of intestinal permeability before and after a gluten load were studied. The study group comprised 27 patients with coeliac disease (mean age 12.3 years) and 19 healthy controls matched by sex and age. Intestinal permeability was studied by measuring the urinary excretion of two sugars, lactulose and L-rhamnose, before and six hours after the ingestion of five palatable biscuits made with 50 g of gluten powder. The patients with coeliac disease had been on a gluten free diet during the previous two years. After the gluten load lactulose and L-rhamnose urinary excretion changed significantly in patients, and a significant increase in the lactulose: L-rhamnose ratio was also observed. No significant changes were observed in the controls. In view of the modification of the three biopsies diagnostic protocol made by the European Society for Paediatric Gastroenterology and Nutrition, permeability tests associated with single gluten challenges may be an added contribution to the accuracy of the diagnosis in childhood.